Pre-cooling moderately enhances visual discrimination during exercise in the heat - Clarke, N. D.; Duncan, M. J.; Smith, M.; Hankey, J. (Journal of Sports Sciences, 2017)
Pre-cooling has been reported to attenuate the increase in core temperature, although, information regarding the effects of pre-cooling on cognitive function is limited. The present study investigated the effects of pre-cooling on visual discrimination during exercise in the heat. Eight male recreational runners completed 90 min of treadmill running at 65% 2max in the heat [32.4 ± 0.9°C and 46.8 ± 6.4% relative humidity (r.h.)] on two occasions in a randomised, counterbalanced crossover design. Participants underwent pre-cooling by means of water immersion (20.3 ± 0.3°C) for 60 min or remained seated for 60 min in a laboratory (20.2 ± 1.7°C and 60.2 ± 2.5% r.h.). Rectal temperature (Trec) and mean skin temperature (Tskin) were monitored throughout the protocol. At 30-min intervals participants performed a visual discrimination task. Following pre-cooling, Trec (P = 0.040; = 0.48) was moderately lower at 0 and 30 min and Tskin (P = 0.003; = 0.75) lower to a large extent at 0 min of exercise. Visual discrimination was moderately more accurate at 60 and 90 min of exercise following pre-cooling (P = 0.067; = 0.40). Pre-cooling resulted in small improvements in visual discrimination sensitivity (F1,7 = 2.188; P = 0.183; = 0.24), criterion (F1,7 = 1.298; P = 0.292; = 0.16) and bias (F1,7 = 2.202; P = 0.181; = 0.24). Pre-cooling moderately improves visual discrimination accuracy during exercise in the heat.